The Effect of Cognitive Behavioral Therapy in Occupational Therapy on Anxiety Levels in Schizophrenia Patients - Prameswara, Dila Juwita; Kuncoro, Bambang; Febrianti, Maya Indah (Jurnal Keterapian Fisik, 2023)
Background: Schizophrenia patients tend to experience anxiety that can hinder the occupational therapy process and occupational function recovery. The purpose of this study was to determine the effect of Cognitive Behavioral Therapy (CBT) on the occupational therapy perspective on the anxiety levels of schizophrenia patients at Grhasia Mental Hospital, Special Region of Yogyakarta (DIY). Methods: This study used a pre-experimental research design with a one-group pre-test and post-test approach. Purposive sampling was used with a sample size of 16 schizophrenia patients. The research instrument used the Zung Self Rating Anxiety Scale (ZSAS) to measure anxiety levels before and after the intervention. Data analysis was performed using the Wilcoxon signed-rank test with the assistance of the SPSS program. Results: The analysis results showed a significant difference between anxiety levels before and after the CBT intervention, with a p-value of 0.001 (p < 0.05). Conclusion: Cognitive Behavioral Therapy has a significant effect on reducing anxiety in schizophrenia patients at Grhasia DIY Mental Hospital. The application of CBT needs to be carried out on schizophrenia patients as a form of occupational therapy intervention to support emotional stability and improve occupational function.